Workplace bullying and its consequence to employee productivity in civil society organisations in Lira City, Uganda - Otema, Opio Denis; Acanga, Alfred Acanga; Mwesigwa, David Mwesigwa (Human Resource and Leadership Journal, 2022)
Purpose: This study sought to investigate the consequence of workplace bullying on employee productivity in CSOs in Uganda. Consequently, three questions were answered, namely: what is the consequence of workplace bullying on employee attendance in civil society organizations? What is the consequence of workplace bullying on employee efficiency in civil society organization? And what is the consequence of workplace bullying on teamwork among employees in civil society organizations? Methodology: This study adopted a literature review method of secondary data from available sources including academic manuscripts, and peer-reviewed journals. Findings: Workplace bullying has negative implications on the productivity of employees, and by extension, negative implications on the productivity of organizations. Workplace bullying diminishes productivity of the organization by causing absenteeism, which deprives an organization of man-hours which should have been put into productivity. It leads to increased absenteeism among employees, which concurs with available studies which observed that the consequences of workplace bullying like absenteeism are liable to affect work performance. Workplace bullying can affect efficiency by altering work tasks and make them difficult or impossible. This way, workplace bullying slowdown work and thereby reduce employees' productivity. In the same vein, bullying makes employees feel that they are not valued or respected, and as a consequence lose their motivation and become less engaged in work, thereby slowing down work pace and by extension, productivity of the organization. Conclusion and recommendations: From the study, bullying contributes a small portion in the variations in slow down among employees in the selected organizations. While bullied employees disguise themselves to continue working, they waste a lot of time attempting to avoid the bully even if bullying does not contribute to significant amount of work slowdown per day, yet cumulative effects of that have negative ramifications on teamwork and employee productivity in general. Unique contribution to policy and or practice: This study used the substantive theory to review the relationship between workplace and bullying and staff productivity. The study has shown significant influences of workplace bullying absenteeism and teamwork. The results validate the significance of the Substantive theory in studying workplace bullying and its influences on staff productivity. Consequently, management of international non-government organizations should not take workplace bullying lightly but should take it as something costly for organizations and therefore should be prevented or redressed by putting in place anti-bullying policies and measures. Also, CSOs should implement procedures for managing both the oppressors and sufferers of workplace intimidation.